2016
DOI: 10.1177/0363546516652615
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Hip Arthroscopy in Radiographically Diagnosed Retroverted Acetabula

Abstract: This study demonstrates that hip arthroscopy can successfully treat femoroacetabular impingement associated with a globally retroverted acetabulum at a minimum 2-year follow-up. Survivorship was 99% at 2 years, with 1 patient requiring further surgery in the form of hip arthroplasty. There was no noted progression of Tönnis grade at final follow-up. The procedure was extremely safe, with a minor complication rate of 3.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 27 publications
(34 reference statements)
0
51
0
Order By: Relevance
“…[64][65][66] Hartigan et al reported a series of 78 patients (82 hips) with global retroversion that underwent arthroscopic treatment. 17 At minimum of 22-month followup (average 39 months), there was a significant improvement in HHS with no worsening of Tönnis grade in 15 hips, and only 1 hip had undergone total hip arthroplasty. At short-term follow-up, hip arthroscopy was an effective treatment for acetabular retroversion.…”
Section: Results Of Arthroscopic Procedures To Treat Acetabular Retromentioning
confidence: 89%
See 2 more Smart Citations
“…[64][65][66] Hartigan et al reported a series of 78 patients (82 hips) with global retroversion that underwent arthroscopic treatment. 17 At minimum of 22-month followup (average 39 months), there was a significant improvement in HHS with no worsening of Tönnis grade in 15 hips, and only 1 hip had undergone total hip arthroplasty. At short-term follow-up, hip arthroscopy was an effective treatment for acetabular retroversion.…”
Section: Results Of Arthroscopic Procedures To Treat Acetabular Retromentioning
confidence: 89%
“…15,16 In contrast, acetabular retroversion is characterized by excess anterior coverage of the femoral head by the acetabulum resulting in femoroacetabular impingement (FAI) and subsequent joint damage. 17 Recent studies have compared results of surgical hip dislocation and PAO to treat acetabular retroversion 2 and investigated hip arthroscopy as a treatment of impingement. 17 As individuals with these conditions commonly present to orthopaedic surgeons, it is important to understand the appropriate nonsurgical and surgical options for these patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the known increased incidence of osteoarthritis in hips with retroverted acetabula, this morphological variant is worthy of attention. 8 Hartigan et al 12 previously reported on the 2-year outcomes of 78 retroverted acetabula treated with hip arthroscopic surgery, describing an improvement in preoperative versus postoperative VAS (5.9 to 2.5), mHHS (65 to 81), HOOS-ADL (69 to 88), and HOOS-Sports (47 to 76) scores. Our results (VAS score decreased from 3.9 to 1.6, HOOS-ADL score increased from 67.3 to 92.3, and HOOS-Sports score increased from 38.9 to 78.7) are comparable with this previous series, with the additional finding that the improvements in PRO scores align with those observed in nonretroverted patients with pincer-type FAI treated in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 32 Recent studies have shown that both hip arthroscopic surgery and anteverting PAO for the treatment of symptomatic acetabular retroversion can lead to significant improvements in patient-reported outcomes (PROs), with a minimal progression of osteoarthritis. 12 , 21 Hartigan et al 12 found that in their case series, the arthroscopic treatment of global acetabular retroversion had a 99% survivorship rate at 2 years, with a minor complication rate of only 3.6%. However, there has been no previous analysis of PROs after the arthroscopic treatment of global acetabular retroversion as compared with outcomes after the arthroscopic treatment of focal pincer-type FAI.…”
mentioning
confidence: 99%